The Location of Foreign Direct Investment Activity: Country Characteristics and Experience Effects - Davidson, William H. (Journal of International Business Studies, 1980)
This article reviews the role of host country characteristics as determinants of foreign direct investment location patterns. It then analyzes the effects of corporate experience on location decisions. Prior experience in a host country is found to increase the firm's priority for projects in that country relative to other investment options. In addition, the experience level of the firm influences the relative importance of different country characteristics in determining location patterns. Inexperienced firms exhibit greater preference for near, similar markets than firms with broader international operating experience.